2014
DOI: 10.2478/s11696-014-0611-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis by UV-curing and characterisation of polyurethane acrylate-lithium salts-based polymer electrolytes in lithium batteries

Abstract: UV-cured caprolactone-based polyurethane acrylate (PUA) polymer blend electrolytes were prepared and characterised. To develop polymer electrolytes suited to ambient temperature, an ionically-conductive and reliable polymer electrolyte based on urethane acrylate resins synthesised from a fluorine-containing di-functional oligomer 6F ethoxylated diacrylate, a di-functional reactive diluent 1,6-hexanediol diacrylate for adjusting the viscosity, and a radical photo-initiator doped with a mixture of lithium salts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…Various UV-cured crosslinked gel polymer electrolytes have been studied so far, primarily including polymerized di-or triacrylate or di-or trimethacrylate esters of PEO with doped lithium salts [3][4][5][6][7][8][9][10][11]. Similar systems based on UV-crosslinked siloxane diacrylate monomers [12,13] or polyurethane-acrylate [14,15] have also been investigated. However, in most of these works, flammable solvents were used, including mainly ethylene carbonate (EC), propylene carbonate (PC), or a standard flammable 1/2 v/v mixture of EC with dimethyl carbonate (DMC) referred to as EC/DMC in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Various UV-cured crosslinked gel polymer electrolytes have been studied so far, primarily including polymerized di-or triacrylate or di-or trimethacrylate esters of PEO with doped lithium salts [3][4][5][6][7][8][9][10][11]. Similar systems based on UV-crosslinked siloxane diacrylate monomers [12,13] or polyurethane-acrylate [14,15] have also been investigated. However, in most of these works, flammable solvents were used, including mainly ethylene carbonate (EC), propylene carbonate (PC), or a standard flammable 1/2 v/v mixture of EC with dimethyl carbonate (DMC) referred to as EC/DMC in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Appetecchi et al (28) reported that the liquid phase decomposed at the surface of the lithium, thereby severely affecting the electrochemical performance, such as the cyclability of the lithium electrode. Thus, the high stability of the composite polymer electrolytes (CPEs) may be due to the absence of any impurities, which is a welcome feature because it permits their use in highvoltage battery applications (29). The flat plateu in Figure 8 with no peaks in the 3.5-4.7-V voltage range confirms the high purity of the prepared composite polymer electrolyte.…”
Section: H + and LI + Conductivities Of The Composite Membranesmentioning
confidence: 86%
“…This approach is preferable to thermal curing in terms of energy saving, safety, high reaction rate, and has found a wide range of industrial applications such as coatings, oil inks, adhesives, dental materials (Ugur et al, 2014;Cheng et al, 2014b;Lee et al, 2011;Yang et al, 2010). However, smallmolecular photo-initiators are usually applied to the UV-curing process and these possess disadvantages such as ready volatility and motion which increase the hazards for workers and affect the properties of the resins.…”
Section: Introductionmentioning
confidence: 98%